2009
DOI: 10.1097/phm.0b013e3181b74698
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Therapy in the Rehabilitation of Lower-Limb Amputation

Abstract: Possible reasons for this large number of side effects could be the lack of selection of patients and the fact that the mirror box therapy was paralleled by a conventional rehabilitation approach targeted to the use of a prosthesis. Warnings on the need to select patients, with regard to their psychologic as well as clinical profile (including time from amputation and clinical setting), and possible conflicting mechanisms between mirror box therapy and conventional therapies are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
2
24
2
2
Order By: Relevance
“…The variety of treatment approaches and attitudes (outlined earlier) reflects the practitioners' professional experience and confidence, and supports the suggestion by Ramachandran and Altschuler [3] that different treatments may suit different patients. The low incidence of dizziness and nausea reported in the current study is in contrast to the high incidence reported in the study by Casale et al [16], a note evaluation with a high withdrawal rate from MVF treatment [16]. The researchers assumed a conflict of body schema (image of normal limb vs prosthesis) to be responsible for the high incidence of irritation in their patients.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The variety of treatment approaches and attitudes (outlined earlier) reflects the practitioners' professional experience and confidence, and supports the suggestion by Ramachandran and Altschuler [3] that different treatments may suit different patients. The low incidence of dizziness and nausea reported in the current study is in contrast to the high incidence reported in the study by Casale et al [16], a note evaluation with a high withdrawal rate from MVF treatment [16]. The researchers assumed a conflict of body schema (image of normal limb vs prosthesis) to be responsible for the high incidence of irritation in their patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Chan et al, 10 2007 Two brief grief reactions Grünert-Plüss et al, 7 2008 Pain increase possible Casale et al, 16 2009 Dizziness, irritation, uneasiness Kawashima and Mita, 11 2009 Client vomited after an increasing feeling of nausea during the first session Darnall and Li, 14 2012 Boredom, increased depression, increase in phantom limb awareness, and phantom limb pain predetermined level of group consensus [18,19]. A number of advantages contributed to the choice of the Delphi Method in this study: feeding back the experts' responses from previous rounds validates and enlarges the data, and rapid clarification can be obtained [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small retrospective chart review from an acute inpatient rehabilitation facility was done. The majority of the patients reported some side effect to the therapy with over half of the patients reporting confusion and dizziness [21]. However, as this was a retrospective review and the subjects were in the acute rehabilitation phase, no conclusions about true side effects or absolute contraindications can be made.…”
Section: Mirror Therapymentioning
confidence: 96%
“…'larının yapmış oldukları retrospektif çalışmada; 33 phantom ağrısı olan hastanın 29'unda endişe, konfüzyon veya baş dönmesi gibi nedenle ayna tedavisini bıraktığı bildirilmiştir. Bu bilgiler doğrultusunda ayna tedavisinin yan etki profilinin belirlenmesi açısından daha sistematik çalışmalara ihtiyaç vardır (24,26).…”
Section: Gereç Ve Yöntemunclassified